SENGKETA HAK ATAS TANAH MELALUI AKTA CESSIE: Studi Kasus Putusan Mahkamah Agung NO 308/PK/PDT2016 jo Kasasi NO 1625 K/PDT/2014 - David Simatupang (Fakultas Hukum Universitas Kristen Indonesia, 2020)
As a material right, land rights are land tenure rights that contain a series of authority, obligations and / or prohibitions for the right-holders to do something about the land that is claimed.